Acute effects of small changes in bicycle saddle height on pedalling coordination - Floria, P.; Ferrer-Roca, V.; Garcia-Lopez, J. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to analyse the acute effects of small changes in bicycle saddle height on pedalling coordination, using vector coding analysis. Lower extremity kinematic data were collected from ten well-trained cyclists while they pedalled at three different saddle heights in random order: preferred, 2% higher and 2% lower than preferred position. A modified vector coding technique and circular statistics were used to quantify coordination for selected hip-knee, hip-ankle, and knee-ankle joint couplings. The results indicate that modifications in saddle height produced moderate alterations in the frequency of movement patterns, which were not enough to alter the classification of coordination. The small modifications observed were in the direction of increasing the frequency of the proximal coordinative pattern as the saddle height decreased.